Still lives: Jewish photography in Nazi Germany - Ashkenazi, ʿOfer (Jewish culture and contexts, 2025)
"This book reveals how Jews used photographs to document their experiences in the face of National Socialism. Based on analysis of over 15,000 images, it explores previously overlooked efforts of Jews to make sense of the changing landscapes of Germany, justify their decisions under Nazism, and communicate their hopes, anxieties, and self-perceptions"